2008
DOI: 10.4049/jimmunol.180.6.4182
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between ICAM-1 and GM-CSF Receptor Signaling Modulates Eosinophil Survival and Activation

Abstract: Reversal of eosinophilic inflammation has been an elusive therapeutic goal in the management of asthma pathogenesis. In this regard, GM-CSF is a primary candidate cytokine regulating eosinophil activation and survival in the lung; however, its molecular mechanism of propagation and maintenance of stimulated eosinophil activation is not well understood. In this study, we elucidate those late interactions occurring between the GM-CSF receptor and activated eosinophil signaling molecules. Using coimmunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
3
22
0
Order By: Relevance
“…7 B ). We previously showed that prolonged survival of GM-CSF-stimulated eosinophils was critically dependent on signals from both the GM-CSF receptor and the ICAM-1 adhesion molecule (48). …”
Section: Resultsmentioning
confidence: 99%
“…7 B ). We previously showed that prolonged survival of GM-CSF-stimulated eosinophils was critically dependent on signals from both the GM-CSF receptor and the ICAM-1 adhesion molecule (48). …”
Section: Resultsmentioning
confidence: 99%
“…Blood donors for eosinophil isolation included three female and five male non-smoking donors (ages 18–50 y) who showed neither asthmatic nor allergic symptoms [5]. Briefly, 1.5 ml of 15% Dextran and 1.5 ml of 0.25 M EDTA was immediately added to 60 ml of collected blood in two 50 ml polypropylene conical centrifuge tubes and allowed to sediment for 30 min at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Most current established methods of preparing eosinophils from peripheral blood utilizing anti-CD16 immunomagnetic beads to remove neutrophils yield a population of cells which is relatively homogenous typically greater than 98% [5]. However, density gradient centrifugation can further distinguish two populations of eosinophils termed “normodense” (specific gravity > 1.085 g/l) and “hypodense” (specific gravity < 1.085 g/l) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Both ERK1/2 and SHP-2 are known to acquire increased phosphorylation after GM-CSF treatment of human eosinophils and play important roles in signal transduction (23). Thus, we investigated whether LXA 4 had any effect on their level of phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Cell culture media, FBS, and antibiotics (penicillin and streptomycin) were obtained from Invitrogen. Human peripheral blood eosinophils were isolated and purified as we previously described (23). FITC-phalloidin was a product of Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%